A Study of Indonesian Perspectives on the Future of the South China Sea: Navigating the Dynamics of Asymmetric Warfare - M. Ganesh Musyaffa A; Priyanto Suharto; Suhirwan Suhirwan (Journal on Education, 2024)
This article explores the shifting global dynamics, focusing on the rise of East Asia, particularly China, and its impact on the Asia Pacific region. The South China Sea (SCS) emerges as a critical area with territorial disputes, notably China's assertive claims and the U.S.'s involvement, leading to heightened tensions. Indonesia's strategic position becomes pivotal in navigating these geopolitical shifts. The analysis emphasizes Indonesia's role in promoting a peaceful SCS region through its free and active policy and ASEAN membership. The Kantian Triangle, rooted in Liberalism theory, serves as a conceptual framework, highlighting the importance of democracy, economic interdependence, and international organizations in conflict resolution. Indonesia's engagement in regional organizations, especially ASEAN, is crucial for resolving SCS conflicts. The ASEAN Outlook On The Indo-Pacific (AOIP) reflects a commitment to inclusive cooperation, prioritizing shared interests. The article underscores Indonesia's efforts to balance relations with the U.S. and China through economic cooperation, contributing to regional stability. Indonesia's economic ties with both nations, guided by the principles of the Kantian Triangle, aim to foster cooperation and reduce the potential for conflict in the SCS. In conclusion, Indonesia's strategic positioning and active diplomatic role positions it as a key mediator, contributing to lasting peace in the SCS amidst the competition between major powers.